UPAYA MENINGKATKAN PEMAHAMAN SISWA TENTANG BAGIAN-BAGIAN TUMBUHAN MENGGUNAKAN MEDIA GAMBAR - Siti Sahronih; Yuce Dahlia (Institut Pendidikan dan Bahasa Invada, 2021)
This research is motivated by the low ability of students' understanding in completing learning about plant parts, so that student learning outcomes are still low. As an effort to improve students' understanding of the parts of plants, namely by using image media. This research method uses Classroom Action Research which consists of four activities, namely: planning, implementation, observation, and reflection. The research subjects were 25 students of class III SDN Karanglayung consisting of 14 male students and 11 female students. This study uses two cycles, where from each cycle there is a significant increase, so that the use of image media can be applied to learning Natural Sciences, namely about plant parts